A methodological approach to design a coil for localised high-frequency induction heating of flat plate. (June 2023) - Biswal, Sunil Kumar; Pal, Sukhomay
High-frequency induction heating (HFIH) is a quick heating technology, mostly used for localised surface treatment. The HFIH process has a portable RLC tank circuit consisting of a fixed size capacitor bank, load-matching transformer and a small size inductor coil. However, the work feasibility of small size inductor coil involves complexity in matching the resonant frequency between the RLC tank circuit and the high-frequency induction power source. Because the resonant frequency of the RLC tank circuit depends on the shape, size and configuration of the considered inductor coil. To address the issue, a numerical model-based approach is proposed herein to do the frequency matching for any coil configurations. Three different coil configurations such as co-direction, single-direction and opposite-direction current coils are considered in the simulation study to optimise their geometry and estimation of resonant frequencies. Based on the derived resonant frequency of the inductor coils, another coupled electromagnetic-thermal model is developed to get the thermal characteristics for a planar heating process of an 8 mm thick mild steel plate. After finding the optimal geometry of all coil configurations, the coils are fabricated and used in experimentation to verify the results of numerical models. It is found that the coil geometry has a significant effect on the resonant frequency and the heating characteristics. In addition, the current work emphasises a systematic approach to address the temperature non-uniformity that arises at the inlet and outlet positions of the workpiece in movable induction heating.